Distribuição geográfica e modelagem de habitat das espécies do gênero Callithrix (Primates, Callitrichidae) - Nicolaevsky, Bertha (2011)
The genus Callithrixcontainssix species of smallarboreal primates found in central andeastern Brazil.The distributions of these species are parapatric with seeming to haveconnection totypes phytoeological training: Callithrix jacchusinhabits in the thorn shrub, C.penicillatadwellsmainly on savanna areas and the other species, C. aurita, C.flaviceps, C.geoffroyi and C.kuhliiaretypical of the Atlantic Forest. Events to introduce some of these species have shown their ability to colonize areas distinct from those where they are native.ThedistributionofCallithrixhasnotbeenreviewedforoverten years and there is a large number of new records for instance, published in specialized literature, that need to be included in biogeographical studies of these species.Moreover, the whereforeof lack of sympatry between Callithrixspecies are not clear,ath the time this matter requiresfurther research.Thus, the aims of this study was to review the geographical distribution of species of Callithrix,investigate the suitable habitat for them to stay beyondgeographical boundaries known and find out if there are regions suitable for more than one species. The occurrence records compiled were georeferenced and the localities were inserted graphically on mapsof the cities, protected areas and vegetation. Subsequently, occurrence data were associated with climatic and topographic variables to produce habitat models forusing the MaxEnt algorithm.A total of 359 localities were compiled and the overlap estimated distribution of polygons displayedthat species exhibit varying degrees of specialismto habitat -from specialistssuch as C.flavicepsable to colonize only four typesdifferent vegetation, to C.jacchusobserved in 25 kinds of different formations.Furthermore, we observed that the vegetation types dense rain forest vegetation and semideciduous forest are present in geographical distribution of the six species.Habitat models showed AUC values greater than 0.9, thenthey can can be considered models with optimum performance. There was overlap between areas suitable for all species.The analysis of occurrence and vegetation associated with habitat modeling results allowed to infer that the boundaries between the areas ofoccurrence, not only coincide with the presence of large rivers, but also with the transition between distinct vegetation formations, and that differentecological adaptive potential of speciesprobably influence their geographical distribution through competitive exclusion